(untitled) (TEL Tempo, Espaço e Linguagem, 2022)
This research aims to conduct a debate on the role of memorialist literature in the construction of a historical narrative in the city of Pouso Alegre/MG. Thus, an important instrument of analysis of society and a documentary framework of relevance to researchers. Advances and debates aim to fill an important scientific role in literary studies.